2016
DOI: 10.11646/phytotaxa.268.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy of Mexican cycads: biogeography, morphology and DNA barcoding corroborate a new sympatric species in Ceratozamia (Zamiaceae)

Abstract: A new species, from the montane region of Los Tuxtlas (state of Veracruz, Mexico), Ceratozamia subroseophylla, is proposed in accordance with the integrative taxonomy framework and through application of the taxonomic circle rationale. Our identification of this new species is the result of a thorough re-evaluation of four formerly described Ceratozamia species, namely: (1) C. miqueliana, with which it overlaps geographically; (2) C. mexicana; (3) C. robusta, which has also been previously seen as morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…Taxonomically, Ceratozamia species are notoriously difficult to identify because of the high morphological species variability, coupled with their very similar morphology , Martínez-Domínguez et al 2016. Hence, field studies of all species of the genus in local populations are useful in furthering the understanding of this variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxonomically, Ceratozamia species are notoriously difficult to identify because of the high morphological species variability, coupled with their very similar morphology , Martínez-Domínguez et al 2016. Hence, field studies of all species of the genus in local populations are useful in furthering the understanding of this variation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, field studies of all species of the genus in local populations are useful in furthering the understanding of this variation. Recent research has suggested the importance of reproductive characters (Martínez-Domínguez et al 2016). Considering descriptions of this characters based only on herbarium specimens may, therefore, be incomplete, ambiguous, and/or distorted, particularly for large strobili.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter region was amplified in Ceratozamia subroseophylla (an ITS region sequence was previously available) and included in the molecular matrix. Choice of markers followed previous publications where they performed best in terms of number of diagnostic sites (Martínez-Domínguez et al 2016, 2017. Amplification products were visualized in 1% ethidium bromide-stained, agarose gels.…”
Section: Biogeographic Information For Specimensmentioning
confidence: 99%
“…However, other contemporary studies have shown that these characters can be highly variable between and amongst populations, which limits species diagnosis (Martínez-Domínguez et al 2016; 2017a, b, c). Other characters commonly used are the direction, form and texture of leaflets and the formation of prickles (Pérez-Farrera et al 2001; Vovides et al 2003).…”
Section: Introductionmentioning
confidence: 99%